Averaging the frequency of the larynx tone in the correlation method of its estimation using the technique of linear prediction - DZIURNIKOWSKI, Andrzej (Archives of Acoustics, 1981)
This paper presents some problems in the effects of averaging the results obtained from the analysis of a speech signal, related to the use of the correlation method of the estimation of the frequency of the larynx tone. The present considerations are concerned with the analysis of a speech signal using the algorithm of linear prediction. The thesis that the results obtained from averaging depend on the parameters of the analysis assumed and the character of a signal is proposed and the reasons for this phenomenon discussed. This dependence must not be neglected in choosing the methods of speech signal analysis in real investigations.